2008
DOI: 10.1080/09602010701748644
|View full text |Cite
|
Sign up to set email alerts
|

Intervention for executive functions after traumatic brain injury: A systematic review, meta-analysis and clinical recommendations

Abstract: A systematic review of studies that focused on the executive functions of problem solving, planning, organising and multitasking by adults with traumatic brain injury (TBI) was performed through 2004. Qualitative and quantitative methods were used to evaluate the 15 studies that met inclusion criteria. Demographic variables, design and intervention features, and impairment and activity/participation outcomes (ICF) (World Health Organization, 2001) were documented. Five randomised control treatment (RCT) studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
189
0
14

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(208 citation statements)
references
References 32 publications
5
189
0
14
Order By: Relevance
“…To date, several studies have demonstrated the importance of preserving frontal metabolism in patients who have suffered a TBI. [13][14] Damage to the frontal lobe and its connections are particularly detrimental and compromise long-term outcome by interfering with the restoration of normal personality, occupational function and community reintegration. Given the recognized importance of the fronto-thalamic connectivity, it was not surprising that the hypometabolism detected in this system appeared to be the most relevant dysfunction of our sample, with the expected resultant clinical implications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, several studies have demonstrated the importance of preserving frontal metabolism in patients who have suffered a TBI. [13][14] Damage to the frontal lobe and its connections are particularly detrimental and compromise long-term outcome by interfering with the restoration of normal personality, occupational function and community reintegration. Given the recognized importance of the fronto-thalamic connectivity, it was not surprising that the hypometabolism detected in this system appeared to be the most relevant dysfunction of our sample, with the expected resultant clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…[32] In the case of the frontal cortex, the differences found between the healthy controls and the patients who had recovered from PTA again highlight the importance of the normal functioning of the frontal cortex in the final outcome after TBI. [13][14] The different evolution of the metabolism of these two cortical structures could also be due to differences in the distribution of lesions detected by structural imaging or to the classification criteria used in this study. It is possible that a classification based on more specific criteria, which are directly related to the functionality of these areas, would have yielded different results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the effectiveness of cognitive rehabilitation is documented within some domains following ABI, there is still a paucity of empirical evidence for the efficacy of interventions for rehabilitation of EF (Cicerone et al, 2011;Rees, Marshall, Hartridge, Mackie & Weiser, 2007; Wilson, 2008). Reviews recommend metacognitive strategy training including self-monitoring and self-regulation as practice standard following ED due to traumatic brain injury (TBI) (Cicerone et al, 2011;Kennedy et al, 2008). Promising results have been reported for (Coull, 1995;Smith & Nutt, 1996).…”
mentioning
confidence: 99%
“…In other populations (including education, learning difficulties and adult literacy) [60][61][62][63][64][65] reading strategies are well researched and have a strong evidence base. Within ABI cognitive rehabilitation, strategy use is a common intervention 91,92 , with strong evidence for metacognitive strategy instruction 93 . It should therefore not be surprising to see clinicians utilising strategies as common practice in the rehabilitation of CCRC deficits.…”
Section: Use Of Reading Strategies In Rehabilitationmentioning
confidence: 99%